Cleavage and polyadenylation: Ending the message expands gene regulation - Neve, J; Patel, R; Wang, Z; Louey, A; Furger, A (Taylor and Francis, 2017)
Cleavage and polyadenylation (pA) is a fundamental step that is required for the maturation of primary protein encoding transcripts into functional mRNAs that can be exported from the nucleus and translated in the cytoplasm. 3′end processing is dependent on the assembly of a multiprotein processing complex on the pA signals that reside in the pre-mRNAs. Most eukaryotic genes have multiple pA signals, resulting in alternative cleavage and polyadenylation (APA), a widespread phenomenon that is important to establish cell state and cell type specific transcriptomes. Here, we review how pA sites are recognized and comprehensively summarize how APA is regulated and creates mRNA isoform profiles that are characteristic for cell types, tissues, cellular states and disease.